Election Turnout Inequality - Insights from Administrative Registers - Bernt Bratsberg; Andreas Kotsadam; Jo Thori Lind; Halvor Mehlum; Oddbjørn Raaum (Center for Economic Studies and ifo Institute (CESifo), 2019)
Using matched administrative election data from Norway, we document gender-specific turnout rates by a range of socio-economic outcomes as well as family relationships and immigrant status. High social rank is consistently associated with higher turnout: we find significant turnout gradients for education, occupational prestige, income, wealth, and parental economic resources during childhood. Turnout among spouses, parents and children, as well as siblings and cousins, are highly correlated, showing strong influences of family factors. Immigrant turnout falls far below that of natives of similar age, even many years after arrival. Turnout among children of immigrants is more similar to that of natives, indicating political integration across but not within generations. Election turnout inequality implies that voters differ from the electorate at large along a number of socio-economic dimensions; we find that such misalignment is similar to that observed in the US.
Keywords: 330; election turnout; administrative register data; turnout inequality